ANALISIS KEUNIKAN SERAT DAN CORAK DAUN CALADIUM MENGGUNAKAN METODE THRESHOLD - Ahmad Faisal Hamidi; Ahmad Baihaki; Muhammad aqiba Zaim (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2023)
Caladium is one type of ornamental plant which is also widely known by the public as taro. The color and pattern of its beautiful leaves make taro a favorite of many people. The taro plant has the scientific name Caladium. Caladium is one of the genera of the taro family or the Araceace family. Caladium has various types, in each type has different fibers and patterns. To determine the type of fiber and pattern of caladium used image analysis pattern with the threshold method,With this method we will be able to know the types of taro plants according to their patterns and fibers that we have read and compared with the method, so that collectors or sellers are assisted in distinguishing them.